Synthesis and antibacterial activity of 1 beta-methyl-2-[5-(1,2-disubstituted ethyl)-pyrrolidin-3-ylthio]carbapenem derivatives. Part III - Cho, Jung-Hyuck; Ahn, Soo-Hyun; Jeon, Heechol; Kim, So Young; Oh, Chang-Hyun (WILEY-V C H VERLAG GMBH, 2006)
The synthesis of a new series of 1 beta-methylcarbapenems having 5-(1,2-disubstituted ethyl)pyrrolidine moiety are described. Their in vitro antibacterial activities against both Gram-positive and Gram-negative bacteria were tested and the effect of substituents on the pyrrolidine ring was investigated. Among them, compound (IIIc) having 1-methoxyimino-2-hydroxyethyl moiety showed the most potent antibacterial activity.
Keywords: BETA-LACTAM ANTIBIOTICS; CARBAPENEM ANTIBIOTICS; THIENAMYCIN; 1-BETA-METHYLCARBAPENEM